State Control Of Electronic Information Resources: Role And Efforts In The Modern Context - Putri Ayi Winarsasi; Mutia Cherawaty Thalib; Mohamad Rivaldi Moha; Nurul Fazri Elfikri (Universitas Trunodjoyo Madura, 2023)
This research focuses on the role and responsibility of the state in controlling and regulating electronic information resources, especially in the scope of e-commerce in Indonesia. In the digital era, the rapid development of e-commerce requires effective and comprehensive regulation to ensure the integrity, security, and growth of this industry. This research discusses several necessary regulations adopted by the Indonesian government, including Law Number 11 of 2008, which was changed to Law Number 19 of 2016 concerning Information and Electronic Transactions, Government Regulation No. 82 of 2012 concerning the Implementation of Electronic Systems and Transactions, Law Number 7 of 2016 concerning Trade, and Bank Indonesia Regulation No.11/12/PBI/2009 concerning Electronic Money. This research shows that these regulations and policies have established a Solid legal framework for e-commerce in Indonesia. However, given the rapidly changing technology and industry dynamics, these regulations and policies must be continuously updated and adapted to new needs. Therefore, the state's role in monitoring industrial developments, adjusting regulations, and educating the public is essential in establishing a fair, safe, and sustainable e-commerce ecosystem. Overall, this research shows that balancing consumer protection and industry growth is critical for the future of e-commerce in Indonesia.